0845 Flow Mediated Dilation and Physical Activity Intensity in Patients with Obstructive Sleep Apnea and Chronic Obstructive Pulmonary Disease Overlap Syndrome. (12th April 2019) - Macrea, Madalina; Oursler, Kris Ann; Martin, Thomas; ZuWallack, Richard; Malhotra, Atul
Abstract: Introduction: Patients who have both obstructive sleep apnea (OSA) and chronic obstructive pulmonary disease (COPD) (Overlap Syndrome, OS) have increased coronary artery disease (CAD) risk. Endothelial dysfunction precedes clinical disease of coronary atherosclerosis and myocardial infarction and can be measured by brachial artery flow-mediated dilatation (FMD). A physically active lifestyle could prevent the development of CAD. Cross-sectional data on the relationship between physical activity (PA) and endothelial dysfunction in OS are lacking. We investigated prospectively the association of leisure-time PA with endothelial dysfunction measured by FMD in patients with OS. Methods: Patients with OS (FEV1/FVC<70 and CPAP therapy) were prospectively enrolled from sleep clinics at the Salem VAMC into an exercise study. FMD was measured with ultrasonography. An FMD cutoff below 10.7% was used to estimate CAD risk as per Schechter et al. PA was quantified during a 7-day period using ActiGraph wGT3X-BT wrist worn accelerometer. The percentage of time spent in sedentary, light and moderate intensity activities was quantified over a 7 day period using ActiLife software version 6 (ActiGraph, Pensacola, FL, USA). Data are expressed as mean (SD). The association between intensities of leisure-time PA and FMD was tested using Spearman rank correlation coefficient (rho). The strength of correlation coefficients was considered strong if rho ≥0.7. Results: The mean age was 64±7 years in 9 male patients enrolled to date. Mean BMI was 31±3kg/m 2 . One patient had mild COPD, 6 had moderate COPD and 3 had severe COPD. FMD was less than 10.7% in 80% of patients. There was no correlation between FMD and age, BMI, severity of COPD or CPAP compliance. There was a strong correlation (rho=0.84, p=0.004) between percentage of time spent in moderate intensity PA and FMD. Conclusion: These research findings suggest that directly-measured physical activity is potentially related to reduced CAD risk, mediated via FMD. Further studies would be needed to confirm these findings. Support (If Any): Department of Veteran Affairs, Rehabilitation Research and Development Service VA Career Development Award to Dr. Macrea